RESEARCH OF COPING STRATEGIES OF LOSS OVERCOMING IN SYSTEMIC PSYCHOLOGICAL SUPPORT OF POLICE OFFICER’S WIDOWS - Rybyk, Larisa (PSYCHOLOGICAL JOURNAL, 2018)
The subjective choice of coping strategies when experiencing loss is based on the individual psychological peculiarities and experience of overcoming difficult life situations. However, any experience of an extreme situation can be divided into three varieties − problem-oriented, emotionally-oriented and avoidance. The basic behavioral patterns of overcoming can also be characterized as instrumental − focused on specific actions and palliative − aimed at emotional reactions regulation. In the situation of loss, no action can solve the problem of the death of a loved one, and control, regulation or suppression of emotions can lead to negative consequences, such as depression or psychosomatic illness. In this context, coping strategies are considered as a synthesis of adequate experience of loss and adaptation to a changed system of life. This is consistent with the concept of a double process of overcoming behavior − a response to stress and, directly, anxiety. The choice of coping strategy complies to the desire for optimal interaction of the individual with his life circumstances and at the same time, the structural and functional organization of the psyche is unchanged, regardless of the type of activity. Key components of the structure of coping strategies − information, activity, resource. Formation of psychological overcoming occurs under the influence of stable determinants integrating the crisis through the prism of individuality. Factors that influence the choice of doping strategy are the structure of the individual, objective living conditions, resources, internality / externality, the implementation of short-term or long-term plans. Personality activities are aimed at creating of the comfortable living environment that activates existing patterns of behavior or creating of a new response paradigm. Formation and timely controlled use of sustainable and situational determinants is foreseen for successful adaptation in the changing conditions of existence, The analysis of widow’s coping strategies, inclusive of the situation of loss, has caused a controversial perception of the adaptability / non-adaptability of individual strategies. Adaptive strategies − preserving self-esteem can lead to suppression of feelings and nervous breakdown, and while working through grief, the main thing are open emotional experience. Non-adaptive strategies − ignoring, as a kind of apathy behavior for resources saving; humility, a necessary factor for the death acceptance, that is, to accept fate. Relatively adaptive strategies - emotional discharge, as a reboot of the body; compensation and distraction help to survive the grief. The results of the research indicate a positive effect of psychological support on the person’s adaptability, namely, in the cognitive sphere, the indicators on the scale of ‘confusion’ and ‘ignoring’ are decreasing; in the emotional sphere, the strategies of ‘suppressing emotions’ and ‘self-excuse’ were less used; in the behavioral sphere indicators of ‘active avoidance’ decreased, but the strategy of ‘constructive activity’ began to be used more often. A comparative analysis of the indicators of the group that participated in the psychological support experiment and the control group gives grounds to conclude that women who decide to manage their loss in dependently, avoid to contact with the trauma primarily, while women who received psychological help, suffer a loss in a more adaptive way. Key words: widows, coping strategies, psychological trauma, personality adaptation.